Prediction of drug concentrations in humans for long-acting injectable suspensions by a semi-mechanical muscle compartment model: a case study of paliperidone palmitate - Yu, Panpan; Zhang, Mengjun; Jin, Xiong; Wu, Keheng; Long, Sihui; Cheng, Shishi; Fu, Long; Xu, Xiao; Liu, Jie; Liu, Dan; Li, Xue; Liu, Bo; et al. (Frontiers in Pharmacology, 2025)
Long-acting injectable formulations, such as paliperidone palmitate extended-release injectable suspension, have been designed to release medicines slowly and sustainably. Developing models that simulate drug release from long-acting injectable formulations in vivo is challenging. A novel approach to modeling and simulating complex and multiphasic drug pharmacokinetics (PK) is provided in this article to facilitate development of long-acting formulations. By segmenting nanocrystalline particles according to their different sizes, the absorption delays of each segment were obtained from the results of the PK study in dogs. In addition to the lag time for each segment, all other parameters, including physicochemical parameters such as drug solubility, density and diffusion coefficient, as well as pharmacokinetic parameters related to clearance, elimination and distribution, were introduced into the model to establish a muscle compartment model for use in humans. By using this model, the injectable suspensions paliperidone samples were predicted to have a long release of 90–100 days in vivo.